2020
DOI: 10.3390/rs12193264
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments to SIF Aid the Interpretation of Drought Responses at the Caatinga of Northeast Brazil

Abstract: Sun-Induced chlorophyll Fluorescence (SIF) relates directly to photosynthesis yield and stress but there are still uncertainties in its interpretation. Most of these uncertainties concern the influences of the emitting vegetation’s structure (e.g., leaf angles, leaf clumping) and biochemistry (e.g., chlorophyll content, other pigments) on the radiative transfer of fluorescent photons. The Caatinga is a large region in northeast Brazil of semiarid climate and heterogeneous vegetation, where such biochemical and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Table 8 lists the predictors and model performance of past SIFrefactoring products. Comparatively, the model performance in this study reached a level on par with recent regional-scale SIF reconstruction products (Bontempo et al, 2020;Guo et al, 2020), i.e., our model R 2 for high and LLG regions reached 0.77 for the June-October period. In addition, we found that for the midlatitude forest and HLG, their R 2 could be increased further when using a more complex algorithm.…”
Section: Comparisons With Other Relevant Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Table 8 lists the predictors and model performance of past SIFrefactoring products. Comparatively, the model performance in this study reached a level on par with recent regional-scale SIF reconstruction products (Bontempo et al, 2020;Guo et al, 2020), i.e., our model R 2 for high and LLG regions reached 0.77 for the June-October period. In addition, we found that for the midlatitude forest and HLG, their R 2 could be increased further when using a more complex algorithm.…”
Section: Comparisons With Other Relevant Methodssupporting
confidence: 62%
“…Similarly, Li and Xiao (2019) used EVI, PAR, vapor pressure deficit (VPD), and air temperature of 0.05 • MODIS to build a global seasonal scale regression model with an R 2 = 0.79, extending the discontinuous OCO-2 detection to 0.05 • global SIF. Bontempo et al (2020) used the 0.05 • MODIS-derived VIs, surface temperature, precipitation rate, soil moisture data, and surface reflectance, along with the rainfall rate and soil moisture product of the Tropical Rainfall Monitoring Mission (TRMM-TMPA), in a regional seasonal scale regression, thereby reconstructing the 0.5 • GOME-2 SIF in northeastern Brazil to 0.05 • , with an R 2 = 0.74. Gensheimer et al (2022) used NDVI, EVI, near-infrared reflectance of vegetation (NIRv), kernel normalized difference vegetation index (kNDVI), MODIS bands, and solar zenith angle (SZA), as well as MFs, to construct a convolutional neural network (CNN), which they named SIFnet (monthly regression at global scale), for non-US regions spanning 2018-2021.…”
Section: Introductionmentioning
confidence: 99%
“…The NAD layers from the AnisoVeg product have been used in previous studies to explore: the climate drivers of the Amazon forest greening (Wagner et al, 2017); the large-scale Amazon forest sensitivity to drought (Anderson et al, 2018); the structure and dominance of bamboo species in southwest Amazon (Dalagnol et al, 2018); the productivity in a flooded forest in eastern Amazon (Fonseca et al, 2019); the productivity and relationship with Sun-Induced Fluorescence over the Brazilian Caatinga biome (Bontempo et al, 2020); the relationships with leaf-age demography in central Amazon (Gonçalves et al, 2020); and the relationships with fire disturbance and SAR-based Vegetation Optical Depth in southern Amazon (Zhang et al, 2021).…”
Section: Prospective Use Of the Datasetmentioning
confidence: 99%
“…Due to the improvements in cloud detection, aerosol retrieval and atmospheric correction, the MAIAC algorithm provides from 4 to 25% more high-quality retrievals than the traditional MOD09 product, with the largest estimate being observed for tropical regions (Lyapustin et al, 2021). Studies have used MODIS MAIAC observations with nadir-normalized geometry to assess Amazonian forests' structure, functioning, and impacts of environmental and climate change (Hilker et al, 2014;Wagner et al, 2017;Anderson et al, 2018;Dalagnol et al, 2018;Fonseca et al, 2019;Bontempo et al, 2020;Gonçalves et al, 2020;Zhang et al, 2021). For instance, such product provided reliable time series of surface reflectance data that allowed to identify largescale communities of bamboo species and their dynamics in the southwest Amazon .…”
Section: Introductionmentioning
confidence: 99%